Integrasi Epistemologi Bayani, Burhani dan Irfani dalam Pembentukan Ilmu Pendidikan Islam Kontemporer - Nurhamidah, Winda Islamitha; Maesaroh, Maesaroh; Balkis, Lutfiah Holifa; Rahma, Aufa Fatchia; Haqiah, Nur Azizatul; Usman, Usman (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
The rapid advancement of science and technology in the twenty-first century has reshaped human conceptions of knowledge and reality, contributing to a global crisis of meaning rooted in secular and positivistic epistemologies that separate truth from moral and spiritual values. Within Islamic education, this tension appears in the dichotomy between religious and worldly sciences, creating fragmentation and imbalance. This study examines the integration of three classical Islamic epistemologies: bayani which is textual and normative, burhani which is rational and empirical, and irfani which is intuitive and spiritual as a conceptual basis for reconstructing the philosophy of Islamic education. Using a qualitative approach through literature analysis of primary and secondary sources from scholars such as al Ghazali and Syed Muhammad Naquib al Attas, the findings show that integrating these epistemologies produces a holistic framework that harmonizes revelation, reason, and spiritual intuition. This model offers an alternative to secular education by promoting intellectual, moral, and spiritual balance and fostering ethically responsible individuals.